Event Review: “NOVILARA DEI PICENI” Walk like a Picenian… - Mauro Fiorentini (EXARC, 2021)
The Iron Age in Italy began in approximately the 9th century BC and, specifically in the modern region known as Marche, ended in the first half of the 3rd century BC, which coincided with the conquering of the territory by the Romans.